Flow behavior of 1.4841 steel in hot compression process - Rajabi, Javad (Penerbit Universiti Kebangsaan Malaysia, 2018)
Hot compression experiments using a dilatometer were carried out in order to study the effects of hot compression parameters on the flow behaviour of 1.4841 steel. Specifically, the effects of the strain rate and the deformation temperature within a temperature range of 950 – 1100 oC, strain rate of 0.001-0.5 s-1and strain value of 0.5 were studied among all the effective hot compression parameters. The results were shown in the actual strain–stress curve. Embedded in the work hardening, recrystallization and recovery theories, the hot compression mechanism was determined by focusing on the flow behaviour patterns of this steel. The sensitivity to strain rate and temperature, activation energy and the Zener – Holloman parameter were also investigated. Critical strains (εc) of 0.2 and 0.35 were calculated for strain rates of 0.001 and 0.01 s-1, respectively. The findings showed that the recrystallization and flow stress fell when a deformation was imposed at a low strain rate and high temperature. A further increase in the strain rate and a decrease in the temperature resulted in a dynamic recovery mechanism as the dominant process. With an increase in the temperature, the strain rate sensitivity increased, and the rise in the strain rate resulted in a decrease in the temperature sensitivity. The temperature sensitivity (ηa) for various strain rates was estimated more precisely to be within the range of 5.3 to 11.2. The QHW was measured and the value was 459.186 kJ/mol.